Home-based transcranial direct current stimulation in dual active treatments for symptoms of depression and anxiety: A case series - Sobral, Mónica; Guiomar, Raquel; Martins, Vera; Ganho-Ávila, Ana (Frontiers in Psychiatry, 2022)
Transcranial direct current stimulation (tDCS) is a potential treatment strategy across some psychiatric conditions. However, there is high heterogeneity in tDCS efficacy as a stand-alone treatment. To increase its therapeutic potential, researchers have begun to explore the efficacy of combining tDCS with psychological and pharmacological interventions. The current case series details the effect of 6 to 10 weeks of self-administered tDCS paired with a behavioral therapy smartphone app (Flow™), on depressive and anxiety symptoms, in seven patients (26-51 years old; four female) presenting distinctive psychiatric disorders (major depression, dysthymia, illness anxiety disorder, obsessive-compulsive disorder, and anxiety disorders). tDCS protocol consisted of an acute phase of daily 30min sessions, across 10 workdays (two weeks Monday-to-Friday; Protocol 1) or 15 workdays (three weeks Monday-to-Friday; Protocol 2). A maintenance phase followed, with twice-weekly sessions for four or three weeks, corresponding to 18 or 21 sessions in total (Protocol 1 or 2, respectively). The Flow tDCS device uses a 2mA current intensity, targeting the bilateral dorsolateral prefrontal cortex. The Flow app offers virtually guided behavioral therapy courses to be completed during stimulation. We assessed depressive symptoms using MADRS-S and BDI-II, anxious symptoms using STAI-Trait, acceptability using ACCEPT-tDCS, and side effects using the Adverse Effects Questionnaire, at baseline and week 6 of treatment. Six patients underwent simultaneous cognitive-behavioral psychotherapy and two were on antidepressants and benzodiazepines. According to the Reliable Change Index (RCI), for depressive symptoms, we found clinically reliable improvement in five patients using MADRS-S (out of seven; RCI: -1.45, 80% CI; RCI: -2.17 to -4.82, 95% CI; percentage change: 37.9%-66.7%) and in four patients using BDI-II (out of five; RCI: -3.61 to -6.70, 95% CI; percentage change: 57.1% to 100%). For anxiety symptoms, clinically reliable improvement was observed in five patients (out of six; RCI: -1.79, 90% CI; RCI: -2.55 to -8.64, 95% CI; percentage change: 12.3%-46.4%). Stimulation was well tolerated and accepted, with mild tingling sensation and scalp discomfort being the most common side effects. This case series highlights the applicability, acceptability, and promising results when combining home-based tDCS with psychotherapy and pharmacotherapy to manage depression and anxiety symptoms in clinical practice.